The Design of Web-Based Training Management Information Systems at PT. Sintech Berkah Abadi - Maimunah​ Maimunah​; Haris Haris; Nurul Priliasari (ADI Publisher, 2021)
ABSTRACT Basically, companies always want to provide the best service, including in providing training in various types of programming languages ??that are owned. A manual system and very slow dissemination of information make the training often very few people want to follow. A computerized training management information system will make it easier for companies to collect data quickly, and also make it easy for prospective applicants to quickly get information about existing training. The management has the duty to manage all matters related to the training, from managing the data of the trainees to the organization of the training. The method used is Extreme Programming (XP) an approach or software development model that tries to simplify the various stages in the development process so that it becomes more adaptive and flexible. The results obtained from this study are a computerized, user friendly training management system. Keywords: Training, Systems, Courses